2020
DOI: 10.5194/tc-14-39-2020
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical modeling of snow failure

Abstract: Abstract. Dry-snow slab avalanches start with the formation of a local failure in a highly porous weak layer underlying a cohesive snow slab. If followed by rapid crack propagation within the weak layer and finally a tensile fracture through the slab, a slab avalanche releases. While the basic concepts of avalanche release are relatively well understood, performing fracture experiments in the laboratory or in the field can be difficult due to the fragile nature of weak snow layers. Numerical simulations are a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
(50 reference statements)
1
24
0
Order By: Relevance
“…the snow viscosity model of Bartelt and von Moos [44], the open-cell foam model for snow [45,46], or other models considering damage healing [3,47,48]. (ii) Models reproducing the microstructure in simplified form with discrete elements (beams, spheres) with some random variations such as the discrete element models [49][50][51]. (iii) Models that use the full 3-D representation of the microstructure obtained by micro-tomography as input for a finite-element model (e.g., [52][53][54]).…”
Section: Models In Snow Mechanicsmentioning
confidence: 99%
“…the snow viscosity model of Bartelt and von Moos [44], the open-cell foam model for snow [45,46], or other models considering damage healing [3,47,48]. (ii) Models reproducing the microstructure in simplified form with discrete elements (beams, spheres) with some random variations such as the discrete element models [49][50][51]. (iii) Models that use the full 3-D representation of the microstructure obtained by micro-tomography as input for a finite-element model (e.g., [52][53][54]).…”
Section: Models In Snow Mechanicsmentioning
confidence: 99%
“…We developed a 3-D discrete element model to investigate the micro-mechanical processes at play during crack propagation in snow fracture experiments. Microscopic model properties were calibrated based on macroscopic snowpack quantities using the method developed by Bobillier, et al 19 . The field data of a PST fracture experiment was recorded during winter 2019 and analyzed with image correlation techniques 12 .…”
Section: Discussionmentioning
confidence: 99%
“…To generate the large DEM simulation domain needed to reproduce the experimental PST, we generated a cell under spatial periodic boundary conditions (base, weak layer and slab) 19 . We then replicated and joined multiple cells (9 in total) to obtain the complete PST system.…”
Section: System Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…As aforementioned, the advantage of this approach is that parameters of the Sticky Hard Spheres model (volume fraction and coordination number) can be directly evaluated based on X-ray tomographic images by matching correlation functions 31 . While several recent numerical studies have analyzed the mechanical response of porous brittle solids like snow based on the real samples' microstructures 18,19,21 , it has been recently shown that simplified structures made of spherical particles can be used to reproduce accurately important features of snow mechanics in the brittle range for different processes: failure initiation 35,36 , crack propagation 9,10 , snowflake fragmentation 37 , wind blowing snow 38 , snow granulation 39 and avalanche impact pressures 40 . One the one hand, this simplification makes us loose important information about the microstructure.…”
mentioning
confidence: 99%